The Role of Richter Circassians in The Study of Living Conditions and Agriculture - Tukhtaboev Mokhirjon Rakhimjonovich; Usmanov Omonali Turgunovich (Scientific Trends, 2023)
This article presents information on the taxonomic composition of the collection belonging to the Richter Cherkezi family (Richter's Salsola) and characterizes the biological properties of medicinal plant species. The article presents information about the state of desert forests in the Southern Kyzylkum region, taxonomic indicators of forest-forming tree and shrub species and the timing of transition to individual phenological phases.
Keywords: diagnostic signs, medicinal plant,s Southern Kyzylkum, desert forests, saksaul, Cherkez, kandim, trees, shrubs, phenological phase.